2016
DOI: 10.3847/0004-637x/827/1/55
|View full text |Cite
|
Sign up to set email alerts
|

INVERSE COMPTON X-RAY EMISSION FROM TeV BLAZAR MRK 421 DURING A HISTORICAL LOW-FLUX STATE OBSERVED WITH NuSTAR

Abstract: We report on the detection of excess hard X-ray emission from the TeV BL Lac object Mrk 421 during the historical low-flux state of the source in January 2013. NuSTAR observations were conducted four times between MJD 56294 and MJD 56312 with a total exposure of 80.9 ksec. The source flux in the 3 − 40 keV range was nearly constant except for MJD 56307, when the average flux level increased by a factor of three. Throughout the exposure, the X-ray spectra of Mrk 421 were well represented by a steep power-law mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…During the faintest state in MJD 56302, its synchrotron component peaks at too low a frequency to make it similar to ISP/LSP. Very recently, Kataoka & Stawarz (2016) reported the detection of a significant excess above 20 keV through NuSTAR observations at this faintest epoch (see also the BeppoSAX observation; e.g., Fossati et al 1999Fossati et al , 2000.…”
Section: The Hard X-ray Excess Of Mrk 421mentioning
confidence: 99%
See 3 more Smart Citations
“…During the faintest state in MJD 56302, its synchrotron component peaks at too low a frequency to make it similar to ISP/LSP. Very recently, Kataoka & Stawarz (2016) reported the detection of a significant excess above 20 keV through NuSTAR observations at this faintest epoch (see also the BeppoSAX observation; e.g., Fossati et al 1999Fossati et al , 2000.…”
Section: The Hard X-ray Excess Of Mrk 421mentioning
confidence: 99%
“…Electrons around γ min will IC synchrotron photons and produce the hard X-ray excess around 20 KeV. We collect this simultaneous broadband SED from Baloković et al (2016) and Kataoka & Stawarz (2016), which are replotted in Figure 1. The synchrotron and SSC components peak at ν p sy ≈ 10 16 and ν p SSC ≈ 10 25 Hz, respectively, which correspond to emissions of electrons with energy around ≈ γ 0 m e c 2 .…”
Section: The Hard X-ray Excess Of Mrk 421mentioning
confidence: 99%
See 2 more Smart Citations
“…3C 66A (Donato et al 2005, Wierzcholska & Wagner 2016; S5 0716+714 (Giommi et al 1999;Tagliaferri et al2003;Donato et al 2005;Ferrero et al 2006;Wierzcholska & Siejkowski 2015); ON 231 (Tagliaferri et al 2000); BL Lacertae (Tanihata et al 2000;Ravasio et al 2002); AO 0235+164 (Raiteri et al 2006); OQ 530 (Tagliaferri et al 2003); 4C +21.35 (Wierzcholska & Wagner 2016). For the well known HBL Mrk 421, Kataoka & Stawarz (2016) found that the X-ray observations from NuStar Satellite is dominated by the highest-energy tail of the synchrotron continuum till 20 keV and the variable excess hard X-ray emission is related to inverse Compton emission in its very low state. All these sources are TeV blazars and have shown variability in γ-bands (Abdo et al 2010).…”
Section: Discussionmentioning
confidence: 99%